2015
DOI: 10.1108/jmp-07-2014-0215
|View full text |Cite
|
Sign up to set email alerts
|

Younger workers’ metastereotypes, workplace mood, attitudes, and behaviors

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…First, our descriptive analyses (presented in Table 1) showed that older age group members perceive less negative stereotyping in their organization regarding older workers’ productivity and reliability (but not regarding personal adaptability) than the younger age group members. Possibly, the younger age groups perceive more negative age-based stereotyping because they are dissimilar to their older co-workers, for example as regards their physical appearance and values/interests (Ryan et al, 2015). In a related vein, older workers may experience less negative age-based stereotyping about themselves (i.e., meta-stereotypes) as they can more easily distance themselves from negative age stereotyping (e.g., “I am not that old”) (ibid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our descriptive analyses (presented in Table 1) showed that older age group members perceive less negative stereotyping in their organization regarding older workers’ productivity and reliability (but not regarding personal adaptability) than the younger age group members. Possibly, the younger age groups perceive more negative age-based stereotyping because they are dissimilar to their older co-workers, for example as regards their physical appearance and values/interests (Ryan et al, 2015). In a related vein, older workers may experience less negative age-based stereotyping about themselves (i.e., meta-stereotypes) as they can more easily distance themselves from negative age stereotyping (e.g., “I am not that old”) (ibid.…”
Section: Discussionmentioning
confidence: 99%
“…When older workers perceive that their age group is negatively stereotyped, they may experience anxiety or anger (King et al, 2008), which in turn may influence their work outcomes (Ryan et al, 2015). In such situations, older workers may find it difficult to hold positive views about themselves, possibly affecting their self-perceived employability.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This notion can impede bidirectional learning processes, because younger employees may feel that when they raise their voices or share their knowledge, it is not appreciated (Tempest, 2003). In such an environment, younger workers are at risk of continuously asking themselves whether others are judging them based on stereotypes (Ryan, King, & Finkelstein, 2015). These beliefs about stereotypes that outgroup members hold against themselves are also referred to as "metastereotypes" (Vorauer, Main, & O'Connell, 1998) and can disrupt interpersonal interactions (King, Kaplan, & Zaccaro, 2008).…”
Section: Intergenerational Learning In Organizationsmentioning
confidence: 99%
“…The age bands used in this study to define younger (18-30 years) and older workers (50+ years) were based on existing research (Finkelstein et al, 2013;North & Fiske, 2016;Ryan et al, 2015).…”
Section: Present Researchmentioning
confidence: 99%